2013
DOI: 10.1177/0192623313482777
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Puberty and Normal Histological Appearances of the Reproductive Organs in Peripubertal Female Göttingen Minipigs

Abstract: In preclinical studies, it is important to know whether the animals used are sexually mature or not. Precise data have not yet been published, however, about the histological features of the female reproductive organs during the peripubertal period or about the age of acquisition of sexual maturity in the minipig. The histological characteristics of the genital organs of female control minipigs from toxicology studies were described and, based on the presence of ovarian corpora lutea, used to assess the age at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 12 publications
4
28
0
Order By: Relevance
“…Unpublished data in Göttingen minipigs supplied by Ellegaard, Denmark, have shown successful mating rates (over 80%) for female minipigs at the ages of 6 months, and minipigs at an average age of 5.6 months have been successfully mated and given birth without complications. These ages are lower than would be expected from the anatomic results of Tortereau, Howroyd, and Lorentsen (2013), in females that were not in the presence of a boar, but are more consistent with the hormonal results of Peter et al (2016), in females that were housed in the same room as adult boars. These results should be confirmed and put into the context of environmental factors such as the age when a boar was introduced, and equivalent data on the breeding performance of young male minipigs should be obtained.…”
Section: Discussionsupporting
confidence: 64%
“…Unpublished data in Göttingen minipigs supplied by Ellegaard, Denmark, have shown successful mating rates (over 80%) for female minipigs at the ages of 6 months, and minipigs at an average age of 5.6 months have been successfully mated and given birth without complications. These ages are lower than would be expected from the anatomic results of Tortereau, Howroyd, and Lorentsen (2013), in females that were not in the presence of a boar, but are more consistent with the hormonal results of Peter et al (2016), in females that were housed in the same room as adult boars. These results should be confirmed and put into the context of environmental factors such as the age when a boar was introduced, and equivalent data on the breeding performance of young male minipigs should be obtained.…”
Section: Discussionsupporting
confidence: 64%
“…It was considered to be approximately 5 months when they have a body weight of approximately 12 kg (Damm Jørgensen, 1998; Creasy, ). However, a recent retrospective study defining sexual maturity as the presence of CL in the ovary revealed that, although sexual maturity can be reached in a few minipigs starting from 5 months of age, only 50% of females of 6.5 months were sexually mature and 100% did not have CL in the ovary until 7.5 months of age (weights around 13 kg) (Tortereau et al, ). Tortereau et al () also reported histologic features of the developing female minipig reproductive tract tissues (vagina, uterus, mammary gland, ovary) and organ weights.…”
Section: Morphologic Aspects Of Female Reproductive System Developmentmentioning
confidence: 99%
“…However, a recent retrospective study defining sexual maturity as the presence of CL in the ovary revealed that, although sexual maturity can be reached in a few minipigs starting from 5 months of age, only 50% of females of 6.5 months were sexually mature and 100% did not have CL in the ovary until 7.5 months of age (weights around 13 kg) (Tortereau et al, ). Tortereau et al () also reported histologic features of the developing female minipig reproductive tract tissues (vagina, uterus, mammary gland, ovary) and organ weights. Specifically, uterine weight of at least 94 g was consistent with sexual maturity; however, ovarian weight provided no correlation.…”
Section: Morphologic Aspects Of Female Reproductive System Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One study detailed the need to be aware of the potential for histologic sexual immaturity in toxicology studies; they compared histological evidence of onset of puberty in Göttingen females with the previously mentioned widely accepted data stating that puberty onset of miniature swine is 4 to 6 months of age and found that only 50% of the females studied at approximately 6.5 months of age could be considered sexually mature based on histological findings (Tortereau, Howroyd, and Lorentsen 2013).…”
Section: Discussionmentioning
confidence: 99%